Saliva cortisol, testosterone and T/C ratio variations during a wrestling competition and during the post-competitive recovery period - Passelergue, P.; Lac, G. (International Journal of Sports Medicine, 1999)
This study presents saliva cortisol (C) and testosterone (T) levels in a group of 15 young wrestlers (national and international) during a two-days competition. Values are compared to references established on a resting day (3 weeks before the competition). Post-competition recovery was studied by recording evening hormonal levels (5.30 pm) for 8 days. RESULTS: C levels increased sharply (about 2.5 fold resting levels) throughout the competition with no further changes in T levels. The rise in C appeared before entering the competition, traducing a striking phenomenon of anticipation. At the end of the competition, C levels fell very quickly (within 1.5 h) to basal value when T rose significantly, resulting in a very high T/C ratio. During the recovery period, C levels corresponded to basal ones and T remained high, resulting in a high T/C ratio (>30% than basal one) till the 5th day. CONCLUSION: Competition resulted in a low T/C ratio, considered as a catabolic phase. The recovery which is associated with a feeling of tiredness and an incapacity to train strenuously recognized by the trainers, paradoxically corresponded to a high T/C ratio (so-called anabolic phase).